Decision support system for agricultural land use and fertilisation optimisation: a case study on barley production in Estonia - Astover, Alar; Roostalu, Hugo; Mõtte, Mati; Tamm, Indrek; Vasiliev, Nikolay; Lemetti, Illar (MTT Agrifood Research Finland, 2006)
The success of the decision support systems, developed within GIS with application of different models, depends on the quality of initial data and the models themselves as well as on the possibilities of their linking. The aim of the present study was to analyse the application of different agro-economic models in a computer-based decision support system, developed for optimisation of agricultural land use and fertilisation, on the example of barley production of Kullamaa rural municipality in Estonia. The algorithms used in the agronomical models were obtained from the regression analysis of numerous field experiments. The calculated new agronomical values serve as a basis for the application of economic models. GIS and modelling remain as two separate systems with the capacity for information exchange between them. Profitability of barley cultivation varied in a very broad range in the study area. The optimal fertiliser amounts established for each field allow increasing crop productivity in the region and at the same time preventing environmental pollution due to production intensification. The proposed decision support system can be further supplemented by several agro-economic models and implemented throughout Estonia.
Keywords: Ka; barley; fertilisation; geographical information system; land use; decision making; risk factors; soil map